PENGEMBANGAN MODEL PELATIHAN KETERAMPILANBERBASIS KEWIRAUSAHAAN: Studi Di Masyarakat Adat Kuta Kabupaten Ciamis. - Sutardi, Tedi (2010)
The research focuses on the development of an entrepreneurship -based skill training model in Kuta's society, Ciamis Regency. This is about how to take advantages of social and economical potential of the society to be explored further in the training model trough a conceptually validated model; how it is implemented; and how far it affects the improvement of income and prosperity of Kuta's sosiety. Those are subjects unveil in this research. The theories used to illuminate the research are: training, adolescence education, empowerment of society and enterpreneurship. The research apllies qualitative research and development approach. Meanwhile the metod used in this research is a descriptive and qusi-experimental desigen. The conceptual model of training is established concerning components such as input, process, output and outcomes in performing the training, i.e planning, performing and evaluating. The planning phase is conducted base on the learning needs of the participants which were discovered trough the process of need assessment, principles of establishing training model, and program evaluation. The performing phase is conducted based on the planinng phase and focused on learning interaction and evaluating the results in regard of whether they will affect the improvement of participants income and prosperity. The learning principles to be considered mainly refer to problema-centered learning, participants-centered learning, paticipants self actualization (including recognition, understanding, sensitivity, tendency, enforcement and learning to each other). The implementation of the training is tested by test I and II trough quasi-experimental method one group pretest-postest design. To test the difference of two pairing values, The Wilcoxon Test is applied. The result in test I and test II showed a significant difference before and after the treatment (training) in the domain of knowledge (cognitive), attitude (affective) and skill. The results showed a conclusión that the entrepreneurship-based skill training model is effective seeing both from the learning results of the participants and the impact it bring about, i.e. improving participants' income and prosperity. The recommendation proposed after conducting the research: to the Departemen of Trade and Industry, it is hoped that the assistance and maintenance of KUBE activity (association in entrepreneurship) in Kuta society are still subject to the development until they can fully stand on their own feet; to the Departement of National Education, it is expected that the society are given non-formal education services in the form of life skill which enables them to have another fringe benefits beside farming. To KUBE (association of entrepreneurship), it is expected that they widen the networking and cooperating with the higher level of entrepreneur.